Main Features and Challenges of Implementing Internal Quality Assurance Within African Higher Education Institutions: The Case of Eduardo Mondlane University - Zavale, Nelson Casimiro; Santos, Luisa Alcantra; da Conceição Dias, Maria (International Journal of African Higher Education, 2016)
Founded in 1962, Eduardo Mondlane University (UEM), Mozambique’s largest and most prestigious university, established an Internal Quality Assurance (IQA) system for the first time in 2013. Based on UEM’s case, this paper examines the features and challenges faced when implementing an IQA system within African higher education institutions. Literature on higher education quality assurance has widely examined the features of, and challenges faced by national QA systems, or by a QA system established across several higher education institutions (HEIs). However, this literature has rarely targeted single HEIs, particularly (African) HEIs that are establishing, for the first time, their IQA systems. Besides, even when IQA at a single HEI is targeted, this is often done by outsiders. Based on reflection-in-action and reflection-on-action, this paper addresses the perspectives of both insiders and outsiders. The authors analyse a system that they have been involved in establishing. The paper’s findings enable to conclude that the main challenges of implementing an IQA system in an African HEI are associated with linking QA to decision-making and to a funding strategy; training human resources and allocating funds for the system to operate and to be sustainable; enabling the system to be assimilated by the university community; and defining measurable and objective quality standards to enable unbiased performance classification. Fondée en 1962, l’Université Eduardo Mondlane (UEM), la plus grande et la plus prestigieuse université du Mozambique, a créé pour la première fois en 2013 un système interne d’assurance qualité (IAQ). A partir de l’étude du cas de l’UEM, cet article examine les caractéristiques et les défis qui attendent les institutions d’enseignement supérieur africaines qui désirent implémenter un IAQ. La littérature sur l’assurance qualité de l’enseignement supérieur a largement examiné les caractéristiques des systèmes nationaux d’AQ (ou de systèmes communs à plusieurs institutions), et les défis auxquels ils sont confrontés. Elle s ‘est cependant rarement concentrée sur des cas uniques d’institutions, notamment des institutions (africaines) qui ont créé pour la première fois leur propre IAQ. Par ailleurs, même quand elle s’attarde sur une institution en particulier, l’analyse est souvent effectuée par des personnes étrangères à l’institution. Fondé sur la réflexion dans l’action et la réflexion sur l’action, cet article présente les perspectives de personnes internes et étrangères à l’établissement. Il permet de conclure que les principaux défis à affronter lors de l’établissement d’un IAQ sont dus à la difficulté de lier l’AQ à la prise de décision et à une stratégie de financement ; à la formation des ressources humaines et l’allocation des fonds nécessaires pour que le système fonctionne et perdure ; à l’assimilation du système par la communauté universitaire ; et à la définition de standards de qualité mesurables et objectifs pour permettre une classification de la performance impartiale.